Fundamentals of business law - Barron, M.L (McGraw-Hill, 1994)
The topic of business law is extensive and covers many areas of law. Authors have found little difficulty in writing a whole text on material dealt with in this text in one chapter. For this reason, this book is not intended as a definitive or exhaustive text on any specific area of law. This is an introductory business law text for entry level students of business, commerce and related area. Its primary focus is not to the 'law' student, but rather, it has been written for students required to study business law as part of their business studies.